The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4209/aaqr.2012.10.0276
|View full text |Cite
|
Sign up to set email alerts
|

The Pearl River Delta Regional Air Quality Monitoring Network - Regional Collaborative Efforts on Joint Air Quality Management

Abstract: In November 2005 the Guangdong and Hong Kong governments established the Pearl River Delta regional air quality monitoring network ("PRD RAQMN"), which represented the first joint regional air pollution and reporting effort in this rapidly developing and heavy-polluted area in southern China. This project has recorded the air quality trends during the 11 th Five-Year Plan (FYP), implemented between 2006 and 2010, and will continue to do so throughout the period of economic development and stringent emission co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Air quality monitoring data (SO 2 , NO 2 , O 3 , and PM 10 ) were collected from the PRD Regional Air Quality Monitoring Network (Zhong et al, 2013b). The network consists of 16 sites with 13 sites in mainland PRD and 3 sites in Hong Kong, which adequately reflect the spatial patterns of air quality in the PRD region.…”
Section: Statistical Datamentioning
confidence: 99%
“…Air quality monitoring data (SO 2 , NO 2 , O 3 , and PM 10 ) were collected from the PRD Regional Air Quality Monitoring Network (Zhong et al, 2013b). The network consists of 16 sites with 13 sites in mainland PRD and 3 sites in Hong Kong, which adequately reflect the spatial patterns of air quality in the PRD region.…”
Section: Statistical Datamentioning
confidence: 99%
“…The site was heavily influenced by the intense air pollutant emissions from Guangzhou and Foshan area in spring, autumn and winter (Zhong et al, 2013;Peng et al, 2014).…”
Section: Observation Site and Periodsmentioning
confidence: 99%
“…However, simultaneous on-line measurements of water-soluble ions of PM 2.5 and related precursor gases (HNO 3 , SO 2 and NH 3 ) are still very rare , and seasonal variations of them has not been reported in this region. In this study secondary water-soluble inorganic ions, including SO 4 2-, NO 3 -and NH 4 + in PM 2.5 , and the related gaseous pollutants including HNO 3 , NH 3 , SO 2 and NO 2 were measured simultaneously at a regional atmospheric supersite in the PRD region of Guangdong Province (Zhong et al, 2013) during four different seasons. The goal of this study was to understand the inter-action of the secondary water-soluble ions and their gaseous precursors and thus to reveal the pollution properties of the secondary inorganic ions in the PRD region, providing scientific support for designing effective fine particle pollution control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent, several measurement studies have also been carried out in China, over which there is an increasing concern of air quality accompanying its fast economic development (e.g., in Lanzhou, Zhang et al, 2009a;Beijing, Liu et al, 2010;Zhang et al, 2011;Xue et al, 2014a). The Pearl River Delta region (PRD) including the adjacent Hong Kong is a hot spot of economic development and air pollution in southern China (Zhong et al, 2013). Previous studies have demonstrated the severity of the photochemical smog problem in this region (Zhang et al, 2007;Zhang et al, 2008;Xue et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%